Moral Values in Surat Luqman and Their Impact on Educational Guidance for Children - Selim , Wafa (Islamic Sciences Journal, 2023)
ABSTRACT The research studied the educational values ​​in Surat (Luqman), deducing these values ​​from the commandments of Luqman, the Wise, to his son. The research came in three sections and twelve demands. The first topic was organized under the title (Allah’s rights in the Surah over man), and this topic included four demands: The first concerns the Faith in Allah Almighty, the second concerns Piety and Fear of Allah Almighty, the third concerns Sincerity to Allah Almighty, and the fourth concerns Thanksgiving to Allah Almighty. Patience, the third is humility and avoidance of arrogance, the fourth is modesty (lowering the voice), and the third topic is entitled (sensory values ​​contained in the surah). The third is entitled Good Deed, and the fourth is entitled Ihsan.